2011
DOI: 10.1002/art.30274
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants in hepatitis C virus–associated mixed cryoglobulinemia: Role of polymorphic variants of BAFF promoter and Fcγ receptors

Abstract: Objective. Mixed cryoglobulinemia (MC) is a hepatitis C virus (HCV)-Conclusion. These results indicate the importance of host genetic background in the development of HCV-MC, suggesting that mechanisms enhancing Ig production and B cell survival may play a relevant role. Genetic Fc␥R variants seem to be crucial to the effectiveness of rituximab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 15 publications
(16 reference statements)
4
50
1
Order By: Relevance
“…Moreover, the frequency of the T allele was significantly greater in HCV-MC patients than in HCV patients without MC (80 versus 36.4 %; P \ 0.001). Similarly, Gragnani et al [39] found in their study a higher prevalence of -871TT homozygosity (31 versus 16 %; P \ 0.001) and greater frequency of T alleles of the BAFF promoter (80 versus 57 %; P = 0.004) in the HCV-MC group than in the HCV group. A significant increase in the serum BAFF concentration was significantly associated with greater frequency of the T allele in HCV-MC patients in their study.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the frequency of the T allele was significantly greater in HCV-MC patients than in HCV patients without MC (80 versus 36.4 %; P \ 0.001). Similarly, Gragnani et al [39] found in their study a higher prevalence of -871TT homozygosity (31 versus 16 %; P \ 0.001) and greater frequency of T alleles of the BAFF promoter (80 versus 57 %; P = 0.004) in the HCV-MC group than in the HCV group. A significant increase in the serum BAFF concentration was significantly associated with greater frequency of the T allele in HCV-MC patients in their study.…”
Section: Discussionmentioning
confidence: 58%
“…BAFF promoter polymorphisms may also be a contributor to MC pathogenesis. The frequency of the -871T allele is greater in HCV patients with than without MC [10,11].…”
Section: Introductionmentioning
confidence: 88%
“…One of the most obvious explanations, the genetic factor, has only recently been seriously reflected when the impact of this disease on chronic HCV infection and its role in predisposing to lymphoid malignancies has been recognized. Since then, some studies have tried to clarify the complex pathogenesis of MC [29] and the most recent have focused on genetics [33][34][35]. A French study stated that BLyS is strongly correlated with B cell proliferation during chronic HCV infection, and it has a strong role in the induction of mixed cryoglobulinemia and other HCV-associated BCP diseases, i.e.…”
Section: Discussionmentioning
confidence: 99%